Masculin féminin - Debout, Jean-Jacques 1942-; Mozart, Wolfgang Amadeus 1756-1791; Maupassant, Guy de 1850-1893; Maupassant, Guy de 1850-1893 (The Criterion Coll., 2005)
Dramatizes the ferment of the 1960's, exploring the reactions of youth to violence, political protest, suicide, birth control and other issues prevalent during the Vietnam era.
Aspect ratio 1.33:1, 16:9 widescreen. - New, restored high-definition digital transfer, supervised by cinematographer Willy Kurant
Orig.: Frankreich, Schweden
Enth. archival 1966 interview with actress Chantal Goya ; new video interviews with Goya, Kurant, and Jean-Luc Godard collaborator Jean-Pierre Gorin, conducted in 2005 ; video discussion of the film between French film scholars Freddy Buache and Dominique Païni ; Swedish television footage of Godard directing the "film within the film" scene ; a 16-page booklet featuring a new essay by film critic Adrian Martin and a reprint of a report from the set by French journalist Phillippe Labro
Keywords: Feature films -- France; Foreign films; Frankreich